Numerical analysis of the effect of vegetation root reinforcement on the rainfall-induced instability of loess slopes - Kong, Kunfeng; Deng, Zixuan; Chen, Feng; Wang, Zheng; Chen, Yiling (Scientific reports, 2025)
Rainfall-induced instability of loess slopes presents significant threats to infrastructure and ecological systems. Vegetation serves as an effective measure to enhance slope stability through mechanical reinforcement by roots and hydrological regulation of soil moisture. The influence of vegetation root system characteristics, including root tensile strength and rooting depth, on the stability of loess slopes subjected to rainfall infiltration is investigated using a finite element model developed in COMSOL®, which couples seepage and mechanical behavior. Rainfall infiltration, pore water pressure evolution, and progressive slope failure are simulated to analyze the stability response. Varying levels of additional cohesion provided by roots and different rooting depths are systematically evaluated. The results indicate that stronger root systems and deeper rooting depths significantly enhance slope stability by increasing the factor of safety, delaying plastic zone development, and reducing displacement. The reinforcement effect becomes more pronounced on steeper slopes, while its marginal contribution diminishes with increasing root depth beyond a certain threshold. These findings provide insights into the role of vegetation in mitigating rainfall-induced slope failures and provide practical guidance for the selection and application of vegetation in ecological slope stabilization projects.